Health-related factors for work participation in persons with spinal cord injury in Finland - Eskola, Kaarina; Koskinen, Eerika; Anttila, Heidi; Tallqvist, Susanna; Bergman, Paula; Kallinen, Mauri; Hämäläinen, Harri; Kauppila, Anna-Maija; Täckman, Anni; Vainionpää, Aki; Arokoski, Jari; Rajavaara, Marketta; et al. (Journal of rehabilitation medicine, 2022)
Objective: To explore work participation and the health-related factors affecting work participation among the Finnish Spinal Cord injury (FinSCI) study population (n = 884).Methods: A cross-sectional explorative observational study in the FinSCI community survey applying Patient-Reported Outcomes Measurement Information System (PROMIS®) forms on Social Health and Global Health. Analyses of socio-demographic and injury-related data were performed.Results: Employment among the study population (n = 452) was 26.5%. Physical, Mental, Social and General Health were better in the employed group compared with work-age persons not working. Logistic regression showed that work participation was related to all health domains, but Physical Health and Ability to Participate in Social Roles and Activities in Social Health were the strongest indicators of likelihood of being at work. Paraplegia and young age were associated with increased likelihood of work participation. Conclusion: The first national survey among people with spinal cord injury in Finland shows low level of employment. The results suggest that pain, physical function, and ability to participate in social roles should be monitored by health and vocational professionals when assessing a person’s likelihood of being in work. Lay abstractThe data source for this study was the Finnish Spinal Cord Injury Study (FinSCI), which collected extensive information from people with spinal cord injury about their health and employment status. A total of 452 responders from the FinSCI survey were included in the current study. The employment rate in the FinSCI study population was low (26.5%) and the majority of those not in work (73.5%) were receiving a disability pension. The analysis of health factors showed that all health aspects were better in the employed group compared with the group who were not working. Physical Health, Ability to Participate in Social Roles and Activities, less severe injury, and young age were associated with likelihood of work participation. This study provides up-to-date self-reported data for the spinal cord injury population and health professionals, helping to identify health-related problems that could be barring employment.